3(2x-7)+4=2(x+1)-15

Simple and best practice solution for 3(2x-7)+4=2(x+1)-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-7)+4=2(x+1)-15 equation:


Simplifying
3(2x + -7) + 4 = 2(x + 1) + -15

Reorder the terms:
3(-7 + 2x) + 4 = 2(x + 1) + -15
(-7 * 3 + 2x * 3) + 4 = 2(x + 1) + -15
(-21 + 6x) + 4 = 2(x + 1) + -15

Reorder the terms:
-21 + 4 + 6x = 2(x + 1) + -15

Combine like terms: -21 + 4 = -17
-17 + 6x = 2(x + 1) + -15

Reorder the terms:
-17 + 6x = 2(1 + x) + -15
-17 + 6x = (1 * 2 + x * 2) + -15
-17 + 6x = (2 + 2x) + -15

Reorder the terms:
-17 + 6x = 2 + -15 + 2x

Combine like terms: 2 + -15 = -13
-17 + 6x = -13 + 2x

Solving
-17 + 6x = -13 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-17 + 6x + -2x = -13 + 2x + -2x

Combine like terms: 6x + -2x = 4x
-17 + 4x = -13 + 2x + -2x

Combine like terms: 2x + -2x = 0
-17 + 4x = -13 + 0
-17 + 4x = -13

Add '17' to each side of the equation.
-17 + 17 + 4x = -13 + 17

Combine like terms: -17 + 17 = 0
0 + 4x = -13 + 17
4x = -13 + 17

Combine like terms: -13 + 17 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| 12a-9a-a=20 | | 2(g-2)-4=4(s+19) | | -8x-10y=16 | | 28000+3000x=2000x+36000 | | 36+78x= | | -2(8+2r)=4(r+8) | | 8y-3x=180 | | 5(4c+1)=5(c+13) | | -16x-20y=12 | | 3x+23=53-x | | 42.9866=3.14r^2 | | J=18-2 | | 2x=(2x)+(2x) | | -6(5-t)=7t | | 6x-5=6-5x | | 2.1+x=7.7 | | -4p-7=5p+2 | | 5(x+5)-8=26-3x-9+8x | | 5.6a=.8(4-a) | | -2(5k-1)=-6(k+1) | | (3-2m)-(3m-2)= | | 25x+20y=220 | | 5xI+5=45 | | 1.6x=4.75 | | -2b-18+5b=-4 | | 3r-6=2r-2 | | 8(x-2)=12 | | 4(1-5x)+6=-26-8x | | 22-4x= | | 5(1+6n)-8(3n+3)=-67 | | 12r=R+1*8 | | 4(2*2+3)=-3(2-1)+31 |

Equations solver categories